Baseline Report of an Urban Gardening Initiative in Dhaka, Bangladesh - Kumar, S.; Schreinemachers, Pepijn; Uddin, Md. Nasir (World Vegetable Center, 2024)
This study is a collaboration across two ongoing projects in Bangladesh: the Dhaka Food Systems Project (DFS), spearheaded by the Food and Agricultural Organization (FAO) and Wageningen University & Research (WUR), and the One CGIAR initiative titled “Resilient Cities Through Sustainable Urban and Peri-urban Agrifood Systems,” for which Work Package 1 is co-led by the World Vegetable Center (WorldVeg). After an initial pilot of an urban gardening program by FAO and WUR, the program is being scaled up to over 5000 urban and periurban households across four city corporations: Dhaka North, Dhaka South, Gazipur and Narayanganj.